Paralinguistic Means as a Component of Speech Culture - Abduzuhurovna, Abduazizova Durdona (Pindus Journal of Culture, Literature, and ELT, 2022)
The article is devoted to the issues of the relationship of paralinguistics with intercultural communication, linguo-culturology, sociolinguistics and cognitive linguistics. The author analyzes the scientific literature on linguistics, cultural studies, pedagogy, discusses the issues of interpersonal relations that depend on the culture of behavior, etiquette of speech and the correct application of paralinguistic phenomena by communicants. The author touches upon the ethical aspect of speech culture, which is important for the correct application of norms and rules of linguistic and non-linguistic behavior, depending on many factors: age characteristics of communicants, social status, communication style (friendly, official, unofficial, etc.), time and place of speech act.